2016
DOI: 10.1016/j.amjcard.2015.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Risk of Atrial Fibrillation in Black Versus White Patients After Coronary Artery Bypass Grafting

Abstract: Obesity has been identified as a risk factor for postoperative atrial fibrillation (POAF) following coronary artery bypass grafting (CABG). However, no studies have addressed the influence of race on this association. A total of 13,594 patients undergoing first-time, isolated CABG without preoperative atrial fibrillation between 1992 and 2011 were included in our study. The association between body mass index (BMI) and POAF was compared by race. Relative risk and 95% confidence intervals were computed using ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Caucasian ethnicity has been found to be a predictor for POAF [5,7,36,37]. A study by Efird et al [37] of 13,594 patients undergoing first-time, isolated CABG found that POAF is significantly associated with white race (95% CI, p < 0.0001).…”
Section: Ethnicitymentioning
confidence: 99%
“…Caucasian ethnicity has been found to be a predictor for POAF [5,7,36,37]. A study by Efird et al [37] of 13,594 patients undergoing first-time, isolated CABG found that POAF is significantly associated with white race (95% CI, p < 0.0001).…”
Section: Ethnicitymentioning
confidence: 99%
“…We further performed a subgroup analysis by type of cardiac operation. Seventeen articles [13-16, 18, 24, 25, 28, 29, 34, 35, 39, 42] reported the association in coronary artery bypass graft (CABG), two articles [19, 36] reported the association in valve surgery, and seven articles [9-13, 30, 31] reported the association in combined types of cardiac surgery. The summary RRs for a 5-unit increment in BMI in the CABG group, valve surgery group, and combined cardiac surgery group were 1.216 (95% CI: 1.21-1.219, I 2 =80%), 1.34 (95% CI: 0.81-2.22, I 2 =84%), and 1.13 (95% CI: 1.06-1.20, I 2 =79%), respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three (34 cohorts) studies (Alam et al, 2011;Banach et al, 2007;Bidar et al, 2014;Bramer et al, 2011;Brandt et al, 2001;Echahidi et al, 2007;Efird et al, 2016;El-Chami et al, 2012;Engelman et al, 1999;Erdil et al, 2014;Gao et al, 2016;Ghanta et al, 2017;Girerd et al, 2009;Gurbuz et al, 2014;Hakala et al, 2009;Ivanovic et al, 2014;Kitahara et al, 2017;Kuduvalli et al, 2002;Lee & Jang, 2020;Melduni et al, 2011;Moulton et al, 1996;Omer et al, 2016;Pan et al, 2006;Perrier et al, 2017;Reeves et al, 2003;Stamou et al, 2011;Stefano et al, 2020;Sun et al, 2011;Tadic, Ivanovic & Zivkovic, 2011 Wong et al, 2015b;Yap et al, 2007;Zacharias et al, 2005) involving 33,271 cases/141,442 patients were included in the dose-response analysis of BMI and POAF. The summary RR for a 5-unit increase in BMI was 1.09 (95% CI [1.06-1.12]) with each weight not exceeding 7%.…”
Section: Dose-response Analysis Of the Effect Of Bmi On Poafmentioning
confidence: 99%